Rehahilitation in territory: buildingparticipation in social life (Revista de Terapia Ocupacional da Universidade de São Paulo, 2001)
This work is meant to present and reflect upon principies for the development of territorial care in rehahilitation for handicaps. First, we consider that the actions of rehahilitation must be part of public policies of care to this sector of population, based on the right to health, on the need for universalization of assistance as part of processes of equalization of opportunities(ONU, 1992). Assistencial policies with such features create conditions to change the logic of philanthropic and beneficent care, typical of current public policies in this area. Second, we consider that the reference of Psychosocial Rehahilitation, taken from the field of mental health care (SARACENO, 1999), provides elements to structure care. Categories as "living", "making social exchanges" and "producing and exchanging goods and values" are brought to this context, in experiments in rehahilitation in a territorial basis, developed in poor suburban districts of the city of São Paulo. Home care, the recognizement and potentialization of the social net and of the support from and to handicaps, along with work and revenue generation programs, open to the participation of ali dwellers of those districts, are some of the features of this work. Actions like these are related to the needs ofinvestment in alternatives for local social development, demanding the active participation of handicaps, their families and neighbours. The support to initiatives of the local Cultural Association aims to make the constitution of participative processes easier, enhancing the dialogue between the needs and the search for collective solutions to problems like: unemployment, fear of violence, lack of room in schools, home confinement, lack of public places for leisure and culture, among others. Citizenship is constituted in this process, as a permanent individual and collective practice.